A preliminary study of turning of composites - Hassan, Nurhafizzah (2008)
Most of the engineering parts are made from metal based materials. Composites have recently become an economic alternative to traditional materials like metals due to their considerable advantages especially in high specific strength and specific stiffness. But, turning of composites is different from turning conventional metals because of the inhomogeneity and anisotropic characteristics of composites. It also depends on the diversity of fiber and matrix properties, fiber orientation, and the relative volume of matrix and fibers. During a turning operation, vibration and noise are generated as a result of the interaction between the rotating work piece and moving cutting force. Therefore, there is a need to understand the dynamic behaviour of composites during machining particularly turning. In this project, the influence factors contributing to surface finish, vibration and noise during turning operation have been established. A mathematical model for the dynamic behaviour of the turning operation is constructed via Rayleigh beam theory and coded into MATLAB tool for simulation. A parametric study is also performed which involves several operational conditions and work piece characteristics to discover their effect on vibration of a work piece (hence the surface finish) through simulation. Results from the numerical simulation generated are found to be consistent with many experimental findings done by the previous researcher.